SUSTAINABLE ISLAND (SAIL): AN INNOVATIVE WAY FOR REACHING A SIGNIFICANT RISE IN INDONESIA WATER, ENERGY, AND FOOD NEXUS INDEX - Hasanah, Nur Aini Iswati (Journal Innovation of Civil Engineering (JICE), 2023)
Indonesia, being an archipelagic country, ranks third in terms of climate risk. Sustainable islands (SAIL) are novel ideas offered as an effective way of achieving Indonesia’s sustainable development while also accelerating climate change mitigation and adaptation. The water, energy, and food (WEF) nexus approach will be used to expand SAIL’s programs. In this nexus, water is the most essential governing factor for the ecosystem and society. Thus, the SAIL program is adopting rainwater harvesting (RWH), a sustainable technology that supplies water with low energy and cost. To irrigate the crops and generate electricity, the island RWH tank is created by impounding surface runoff over natural landscape depressions equipped with a hydrokinetic power system. An RWH system with a pico-hydropower system is installed on the roofs of all island buildings for both household water consumption and electricity generation. The immediate implementation of the SAIL concept promises to boost Indonesia’s WEF nexus index. Keywords: Island; Nexus; RWH; Sustainability; WEF.